Analysis Of The Application Of The Principle Of Pacta Sunt Servanda In Judges' Decisions On Debt Disputes Based On Unwritten Agreements - Lia Amaliya; Farhan Asyhadi; Ahmad Saprudin (Ilmu Hukum Prima (IHP), 2026)
Unwritten debt agreements can cause various problems in the future. One of them is uncertainty regarding the contents of the agreement. One of the most fundamental principles in contract law is the principle of pacta sunt servanda or the principle of legal certainty. This principle relates to the consequences of the agreement. The purpose of this study is to determine the legal provisions related to debts made unwritten based on contract law and to determine the judge's considerations in applying the principle of pacta sunt servanda to debt disputes based on unwritten agreements. This study uses a normative juridical research type. The conclusion in this study is that a valid agreement is an agreement that has fulfilled the requirements for a valid agreement in accordance with Article 1320 of the Civil Code and will have legal consequences for the parties who made it. One of the legal consequences that binds the parties is Article 1338 paragraph (1) of the Civil Code which relates to the principle of Pacta sunt servanda.